American MNEs: In Search of Legitimacy When You’re WEIRD - VanSandt, Craig V.; Mitchell, Matthew C.; Sud, Mukesh (Journal of Management Policy and Practice, 2019)
Presuming that American Multinational Enterprises (AMNEs) prefer to be viewed as legitimate, socially responsible firms in their host countries, we seek to provide answers to the question of how they can best determine ethical standards when faced with multiple, frequently conflicting operating environments? After exploring many of the reasons why identifying and understanding hosts’ moral matrices is extremely confounding, the authors review prior and existing efforts to bridge them and suggest specific steps that AMNEs can employ to better accommodate their ethics to the vastly different cultures in which they operate.